The Relationship between Physical Activity, Self-Perceived Health, and Cognitive Function in Older Adults - Dostálová, Radka; Stillman, Chelsea; Erickson, Kirk I; Slepička, Pavel; Mudrák, Jiří (Brain sciences, 2021)
There are consistent associations between physical activity and self-perceived health. However, it is not clear whether associations between self-perceived health and participation in physical activity could be accounted for by associations with cognitive function. In the present study, we examined whether associations between physical activity and cognitive functioning could explain the variability between physical activity and self-perceived health. A sample of 204 older adults performed three cognitive tests selected from the Vienna test system battery: The Determination, Cognitrone, and Visual Memory tests. These tests measure general processing speed, attention, and visual memory, respectively. Participants also completed the 12-item Short Form Health Questionnaire SF-12 to measure perceived health, and the Physical Activity Survey for the Elderly to measure physical activity. Linear regressions and the PROCESS macro for SPSS were used to test our hypotheses. Consistent with our hypotheses, processing speed accounted for significant variance in the relationship between physical activity and self-perceived health. This suggests that cognitive processing speed might be an indirect path by which physical activity relates to enhanced health perceptions. The results demonstrate that associations between physical activity and self-perceptions of health are related to a fundamental cognitive process.
Keywords: Vienna test system; cognitive function; processing speed; aging; self-perceived health; physical activity